In spies we trust the story of Western intelligence - Jeffreys-Jones, Rhodri (Oxford University Press, 2013)
"In Spies We Trust reveals the full story of the Anglo-American intelligence relationship - ranging from the deceits of World War I to the mendacities of 9/11 - for the first time. Why did we ever start trusting spies? It all started a hundred years ago. First we put our faith in them to help win wars, then we turned against the bloodshed and expense, and asked our spies instead to deliver peace and security. By the end of World War II, Britain and America were cooperating effectively to that end. At its peak in the 1940s and 1950s, the 'special intelligence relationship' contributed to national and international security in what was an Anglo-American century" -- Provided by publisher.